The The DF-ZF hypersonic glide vehicle and what it reveals about China's defense innovation system (Journal of the Spanish Institute for Strategic Studies, 2023)
On July 27, 2021, a test was carried out in China with the DF-ZF hypersonic glide vehicle (HGV), which circled the Earth before reaching its target and caused certain US authorities to describe the situation as “concerning” (Sevastopulo, 2021). China's hypersonic weapons program has attracted a great deal of global attention and research interest in recent years. China's development of a hypersonic weapons system is relevant because of what it provides for the People’s Liberation Army (PLA), but even more so because of what it could mean in terms of China's defense technology innovation capability. This article investigates the technological project that gave rise to the DF-ZF HGV, and analyzes, based on T. M. Cheung’s (2021: 775-801) defense innovation systems model, the main factors of the Chinese system to find its potential strengths and weaknesses.
Keywords: China; Innovation; Technology; Military; Hypersonic; DF-ZF; HGV; PLA